Institutional education policies and alumni career outcomes in Indonesian state maritime institutes - Titis Ari Wibowo; Eleonora Sofilda; Tri Kunawangsih (Research and Development in Education (RaDEn), 2026)
Background-Indonesian state maritime universities face persistent questions about whether institutional education policies adequately shape the career readiness of graduates entering the shipping transportation industry. Objectives-This study examines how three policy domains — teaching professionalism, curriculum quality, and leadership effectiveness — are understood by stakeholders to shape alumni career outcomes across eight Indonesian state maritime universities. Method-A multi-site qualitative policy inquiry was conducted with 75 purposively selected participants from five stakeholder groups. Data were collected through semi-structured interviews, focus group discussions, and institutional document analysis, and analysed using reflexive thematic analysis (Cohen's kappa = 0.78). Results-Teaching professionalism shaped career readiness through two pathways: competency development and professional socialisation. Curriculum quality influenced outcomes primarily through competency formation, with industry alignment and learning outcome clarity as critical inputs. Leadership effectiveness operated as a contextual enabler rather than a direct career determinant. Industry executives consistently assigned lower effectiveness ratings than all other stakeholder groups across all three domains. Conclusions-Systemic interdependence among the three policy domains argues for integrated, rather than isolated, reform strategies addressing teaching quality, curriculum responsiveness, and leadership governance simultaneously.